Đôi nét về Quận Tây Hồ - Vũ, Hoài Phương; Nguyễn, Thị Phượng; Phan, Thị Thúy Hạnh (Thông tấn, 2012)
Giới thiệu 41 di tích đã được xếp hạng Di tích Lịch sử - Văn hóa, di tích Cách mạng tai Quận Tây Hồ, Hà Nội.